Biblical Motifs in the Poem Series ‘Das geistliche Jahr’ of A. von Droste-Hulshof - Bilous, Natalia; Білоус, Наталя Володимирівна; Белоус, Наталья Владимировна (My University, 2018)
The article is devoted to the study of biblical motifs in one of the most famous poem series of A. von Droste-Hulshof, which, at the same time, is the most expressive in the poet’s work, both because of the content point of view, and due to its unique aesthetic palette. Droste’s lyrical image is characterized by poetic program diversity and speech-intonation means richness, which serve as the basis for semantical emphasizing of the author’s appeal to a reader. The article presents the analysis of the rhythm features, sound pattern and vocabulary expressive means as components of the expected effect of biblical motif instructiveness aimed to influence consciousness of author’s contemporaries.
Keywords: christian poetry; rhythm; sound pattern; biblical image